2009
DOI: 10.1021/jp905052h
|View full text |Cite
|
Sign up to set email alerts
|

Reactivity of C2H5+ with Benzene: Formation of Ethylbenzenium Ions and Implications for Titan’s Ionospheric Chemistry

Abstract: The reaction of ethyl cation with benzene has been investigated in a combined experimental and theoretical approach. Under single collision conditions, proton transfer affording protonated benzene concomitant with neutral ethene represents the major reaction channel. From pressure-dependent measurements, an absolute cross section of 7 +/- 2 A(2) at hyperthermal energies (about 1.0 eV in the center of mass frame) is derived for this channel, from which a phenomenological rate constant of about 2.9 x 10(-10) cm(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…[] and Zabka et al . [] requires that the electron dissociative recombination rate coefficient for HCNH + be increased by at least a factor of 10 (if this is really the explanation for the high electron densities). The required increased loss rate could be due to processes leading from HCNH + and C 2 H 5 + to higher mass ion species, followed by increased recombination.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[] and Zabka et al . [] requires that the electron dissociative recombination rate coefficient for HCNH + be increased by at least a factor of 10 (if this is really the explanation for the high electron densities). The required increased loss rate could be due to processes leading from HCNH + and C 2 H 5 + to higher mass ion species, followed by increased recombination.…”
Section: Discussionmentioning
confidence: 99%
“…4. Using the chemical reaction pathways of Anicich and McEwan [1997], McEwan and Anicich [2007], and Vuitton et al [2006Vuitton et al [ , 2007 with updated reaction rate coefficients observed by Edwards et al [2008] and Zabka et al [2009] requires that the electron dissociative recombination rate coefficient for HCNH + be increased by at least a factor of 10 (if this is really the explanation for the high electron densities). The required increased loss rate could be due to processes leading from HCNH + and C 2 H 5 + to higher mass ion species, followed by increased recombination.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ion‐neutral reaction production and loss is given by PiIN=jkj[Ij][nj] LiIN=jkj[nj], where k j is the ion neutral reaction rate, I j is the reactant ion density, and n j is the reactant neutral density. The reactions used come from the model of Vuitton et al [2007] with the additional reactions of methylenimine (CH 2 NH), propionitrile (C 2 H 5 CN), and benzene measured by Edwards et al [2008] and Zabka et al [2009]. A diagram of the primary chemical processes is shown in Figure 5.…”
Section: One‐dimensional Photochemical Modelmentioning
confidence: 99%
“…[34][35][36][37][38] This information facilitates the design of biomimetic catalysts and new drugs as well as a better understanding of protein folding and function. 8,9,19,22,[39][40][41] Most of the previous studies of cation-π interactions with organic cations have used ammonium derivatives [19][20][21][22] and small cations 26,30,[42][43][44] as the probe molecule. It is known that coordinatively saturated cations interact with aromatic rings in a different manner than non-coordinatively saturated carbocations.…”
Section: Introductionmentioning
confidence: 99%